Interactive Game Learning Media Based on Canva on Five Sensory Materials for Grade IV Elementary School - Vitasha Geushiria Aluintany; Kurniana Bektiningsih (Universitas Pendidikan Ganesha, 2024)
Problems in the IPAS learning is students easily get bored with media that is monotonous and lacking in variety, resulting in a lack of student interest in paying attention to the material being presented by the teacher. So, teachers must create more interesting methods in the learning process so that students are more motivated in improving learning outcomes. This study aims to develop interactive game learning media on the five sensory materials for 4th grade of elementary school. This research is included in development research using the Borg and Gall model which only has up to 8 stages, because it is adjusted to the needs and time of the research. The subjects of this study consisted of fourth grade students and fourth grade teachers, a team of expert validators and researchers. Data collection methods are by observation, tests, questionnaires, and interviews. Data analysis techniques use initial data analysis, product analysis, and final data analysis. The research results obtained were the media expert validation test of 85% (feasible), the material expert validation test of 83.5% (feasible), and the results of the effectiveness test showed that in the before and after values there was an increase in the average knowledge value. So, Canva-based interactive learning media has good qualifications, is feasible and effective for use in carrying out the learning process.